2020
DOI: 10.1007/s12144-020-00957-0
|View full text |Cite
|
Sign up to set email alerts
|

Modelling students’ academic confidence, personality and academic emotions

Abstract: The research presented here is founded on the Big Five trait approach to personality which has been shown to be related to academic success, students' academic confidence or self-efficacy and the emotions related to academic achievement.To explore whether Personality characteristics would be differentially associated with Academic Confidence and both would jointly predict Academic Emotions.A bespoke online platform was used to survey undergraduate students in two Spanish universities. The data was used to asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 36 publications
2
16
0
Order By: Relevance
“…While Conscientiousness positively predicted the Deep Approach and negatively predicted the Surface Approach and its components, Neuroticism positively predicted the SA approach and its components. These results are similar to those reported in previous research, where these two factors appear as protective vs. risk factors with respect to achievement [14,49,51,52,59,81,82]. These results remain unchanged in the three situations analyzed (class, study, testing); This would suggest a constant effect of personality factors on motivation, with either positive or negative directionality [83].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…While Conscientiousness positively predicted the Deep Approach and negatively predicted the Surface Approach and its components, Neuroticism positively predicted the SA approach and its components. These results are similar to those reported in previous research, where these two factors appear as protective vs. risk factors with respect to achievement [14,49,51,52,59,81,82]. These results remain unchanged in the three situations analyzed (class, study, testing); This would suggest a constant effect of personality factors on motivation, with either positive or negative directionality [83].…”
Section: Discussionsupporting
confidence: 90%
“…Recent research has reported a consistent relationship between the Big Five model and achievement emotions. The conscientiousness factor predicts positive achievement emotions, while neuroticism predicts negative emotions [58,59].…”
Section: Big Five and Achievement Emotionsmentioning
confidence: 99%
“…Overall, study's results are in line with contemporary research that underline the important role of more individual characteristics in students' learning (Karagiannopoulou et al, 2020;King & Gaerlan, 2014;Sander & de la Fuente, 2020). Adult attachment styles may function as internal motivators that influence goals and targets in one's life, going beyond important relationships (Blalock et al, 2015).…”
Section: Anxious Style and Learningsupporting
confidence: 84%
“…Recent literature suggests that distal individual characteristics may influence students' academic emotions (King & Gaerlan, 2014;Sander & de la Fuente, 2020).…”
Section: Rationale Of the Studymentioning
confidence: 99%
“…Academic confidence has also appeared as a predictor of coping strategies and achievement ( Kirikkanat and Kali-Soyer, 2018 ), as well as predicting confidence in learning ( Shoemaker, 2010 ). More recently, it has been found in association with and a positive predictor of positive achievement emotions, as well as negatively predicting negative emotions ( Sander and de la Fuente, 2020 ).…”
Section: Introductionmentioning
confidence: 99%